Rot, the cutest in the world - Clanton, Ben (New York Atheneum Books for Young Readers, 2017)
Rot, a mutant potato, enters a "Cutest in the World" contest but worries when he sees his competition.
Keywords: Beauty, Personal -- Juvenile fiction -- Contests -- Juvenile fiction -- Self-esteem -- Juvenile fiction